Analisis Pengaruh Keterlambatan Pengurusan Jenazah di Desa Suka Maju - Said Muhammad Fadhi; Qurrata A’yun Sinaga; Aggridita Agita Pasaribu; Windi Arningsih Nainggolan; Hasrat Efendi Samosir (LPPM Institut Nasional Laa Roiba Bogor, 2023)
There are several important things in Islamic teachings that must be done as soon as possible, including taking care of the corpse, serving food when guests arrive, marrying off a girl whose soul mate has arrived, paying off debts when they are due and repenting when committing small or major sins. The law of taking care of the corpse is fard kifayah. The management of the corpse must be expedited as quickly as possible. This is necessary because goodness is good for the corpse itself. In Suka Maju village, Pahae Jae sub-district, there are frequent delays in processing the bodies. In connection with this, the researcher analyzed the causes of delays in the management of corpses in Suka Maju Village and solved the problem so that there were no more delays in the management of corpses. Keywords: Islamic Teachings, Fardhu Kifayah, Training, Counseling, Body Management..